Participatory Heritage Documentation: Low-cost Photogrammetry of Decayed Historic Buildings in the Medina of Tunis - Albuerne, Alejandra; Cruz, Mara (International Society for Photogrammetry and Remote Sensing, 2025)
This paper presents a low-cost, community-led documentation approach for endangered historic buildings in the Medina of Tunis, a UNESCO World Heritage Site facing significant conservation challenges. Focusing on Fondok El Henna—an abandoned caravanserai in a state of advanced decay—the study explores how image-based photogrammetry can be employed in resource-limited contexts through collaboration between local civil society and academic partners. Using available photographic equipment and remote training, the project successfully documented the building’s façade and assessed its condition. The process relied on a modular workflow that combined field data collection by a locally trained team with remote data processing by heritage experts. Despite limited access to technical infrastructure and computing resources, the method proved effective in producing accurate 3D models and identifying key agents of deterioration, including water ingress, biological growth, and human-induced damage. The scientific contribution of this work lies in demonstrating that affordable photogrammetry can be adapted for fragile urban environments, supporting both heritage conservation and community empowerment. The paper offers a replicable methodology that lowers technical barriers and enhances local capacity, while also highlighting the roles digital documentation can play in advocacy, conservation planning, and memory preservation. This approach provides a meaningful, scalable model for documenting neglected heritage in similar contexts globally, particularly where conventional resources and institutional support are limited.
Keywords: Low-cost photogrammetry; Built Heritage documentation; Capacity building; Remote training; Condition Assessment; Medina of Tunis; 33 Ciencias Tecnológicas; ODS 9 - Industria, innovación e infraestructura